2002
DOI: 10.4049/jimmunol.168.6.2914
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Effector Functions Controlled by Bruton’s Tyrosine Kinase Are More Crucial Than the Cytokine Balance of T Cell Responses for Microfilarial Clearance

Abstract: Macrophages from X-linked immunodeficient (xid) mice lacking functional Bruton’s tyrosine kinase (Btk) show poor NO induction and enhanced IL-12 induction, and contribute to delayed clearance of injected microfilaria (mf) in vivo. We now show that Btk is involved in other macrophage effector functions, such as bactericidal activity and secretion of proinflammatory cytokines (TNF-α, IL-1β), but not the T cell-directed cytokine IL-12. Induction of some transcriptional regulators of the NF-κB family, crucial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 57 publications
6
93
0
Order By: Relevance
“…Btk has also been shown to regulate NF B activation via activation of protein kinase C ␤ and the I B kinase complex (7,35). The possibility that Btk may be involved in LPS signaling was suggested by a recent study in xid mice, which implicated Btk in macrophage effector functions in response to LPS (12). Macrophages from xid mice showed poor NO induction and reduced production of the proinflammatory cytokines IL-1␤ and tumor necrosis factor ␣.…”
Section: Discussionmentioning
confidence: 96%
“…Btk has also been shown to regulate NF B activation via activation of protein kinase C ␤ and the I B kinase complex (7,35). The possibility that Btk may be involved in LPS signaling was suggested by a recent study in xid mice, which implicated Btk in macrophage effector functions in response to LPS (12). Macrophages from xid mice showed poor NO induction and reduced production of the proinflammatory cytokines IL-1␤ and tumor necrosis factor ␣.…”
Section: Discussionmentioning
confidence: 96%
“…The mice were injected intraperitoneally with 1 ml of 4% sterile thioglycolate broth, and after 3 days, peritoneal macrophages were isolated as described earlier (35,36). The animal experiments were conducted at the National Institute of Nutrition, Hyderabad, India, upon approval by the Institutional Animal Ethics Committee of the National Institute of Nutrition, Hyderabad, India.…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies have provided a more general role for Btk in immune regulation. Studies in Xid peritoneal macrophages have shown reduced responses to lipopolysaccharide (LPS) stimulation, with tumor necrosis factor ␣ (TNF␣) and IL-1␤ production decreased and macrophage effector functions impaired (5). We have shown that Btk is recruited to the LPS receptor Toll-like receptor-4 (TLR4) where it is activated and is required for NFB activation (6).…”
mentioning
confidence: 99%